Rediseño del CETAD “La Estancia” para mejorar la calidad de vida de los pacientes y los trabajadores, ubicado en la parroquia Los Andes – Patate - Haro Fonseca, Josue Israel (2023)
Alcoholism and drug addiction seriously affects the health and integrity of the person who consumes, but it also affects their entire family, and society. In Ecuador, thousands of young people use drugs, in addition to the fact that there are many elderly people in a state of abandonment and alcoholism, people who psychologically find it very difficult to recover and who receive little or no help, and who also affect the development of society, invading important urban areas of tourism and economy. Given this problem, the only CETAD in the "La Estancia" area adapted to an abandoned school in Patate, which aims to help all people with addiction problems but who also have various needs for a better coexistence and rehabilitation, for this reason For this reason, the redesign was proposed, for this reason it is important to determine the conditions that allow strategic and effective methods to be proposed for a correct rehabilitation in patients, this through a spatial improvement with comfort and sensory effect that generates warmth and positivism in all the people who interact within CETAD. This is how the feasibility of the project and its benefit for people with addictions, their families and for the whole of society are cemented.